2022
DOI: 10.3390/su14148521
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization-Based Approach to Evaluate the Operational and Environmental Impacts of Pick-Up Points on E-Commerce Urban Last-Mile Distribution: A Case Study in São Paulo, Brazil

Abstract: Online sales have steadily increased in recent years. Unlike the traditional retail shopping model, e-commerce must deliver custom orders to highly dispersed locations. Consequently, negative effects have been observed in large urban and densely populated areas, such as congestion and pollution. Pick-up points (PPs) are fast-growing solutions that provide parcel delivery and picking services at diverse locations throughout major city centers. This paper describes an optimization-based approach aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Because of the greater popularity of online shopping in recent years, an increasing number of packages must be delivered with a higher frequency and lower consolidation [7]. Nevertheless, transportation companies focus on maximizing their profits and consumer satisfaction; they generally ignore the negative impact on urban areas bought by increasing road deliveries, especially in terms of environmental impact [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the greater popularity of online shopping in recent years, an increasing number of packages must be delivered with a higher frequency and lower consolidation [7]. Nevertheless, transportation companies focus on maximizing their profits and consumer satisfaction; they generally ignore the negative impact on urban areas bought by increasing road deliveries, especially in terms of environmental impact [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The final stage of delivery is considered a significant hurdle for e-commerce industry leaders and their expansion efforts, primarily due to various inherent factors. Ranging from delayed delivery time to return of the express packages, for example, requires logistics companies to deliver two or more times, which induces additional transportation costs, labor force, and carbon dioxide emission [7]. Meanwhile, failed delivery is also a leading contributor to increased environmental pollution.…”
Section: Factors In Last-mile Delivery To Cause the Environmental Impactmentioning
confidence: 99%
“…Parcel lockers, also called pickup points [91], offer a promising solution to some of the challenges posed by LMD for enhanced efficiency, reduced costs, and minimized environmental side effects [92][93][94]. In this case, distributors deliver parcels to appropriate lockers and inform the customers.…”
Section: Parcel Lockersmentioning
confidence: 99%
“…Silvestri et al [ 4 ] in their study for the optimization of networked goods migration in urban stores pointed out that a shared information-based model of networked goods migration can reduce the pollution generated during transportation and thus its associated externalities. Masteguim and Cunha [ 5 ], on the other hand, conducted a study on the impact of pickup points on last-mile delivery and showed that reasonable delivery points can circumvent more waste of resources. In addition, Hailemariam et al [ 6 ] found that income inequality is positively correlated with carbon emissions, thus achieving a fair distribution of benefits is also essential to promote a low-carbon economy.…”
Section: Introductionmentioning
confidence: 99%